Minnesota field population of western corn rootworm (Coleoptera: Chrysomelidae) shows incomplete resistance to Cry34Ab1/Cry35Ab1 and Cry3Bb1. (February 2017) - Ludwick, D. C.; Meihls, L. N.; Ostlie, K. R.; Potter, B. D.; French, L.; Hibbard, B. E.
Abstract: In the United States of America, the western corn rootworm, Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae), is commonly managed with transgenic corn ( Zea mays L.) expressing insecticidal proteins from the bacteria Bacillus thuringiensis Berliner (Bt). Colonies of this pest have been selected in the laboratory on each commercially available transformation event and several resistant field populations have also been identified; some field populations are also resistant. In this study, progeny of a western corn rootworm population collected from a Minnesota corn field planted to SmartStax ® corn were evaluated for resistance to corn hybrids expressing Cry3Bb1 (event MON88017) or Cry34/35Ab1 (event DAS‐59122‐7) and to the individual constituent proteins in diet‐overlay bioassays. Results from these assays suggest that this population is resistant to Cry3Bb1 and is incompletely resistant to Cry34/35Ab1. In diet toxicity assays, larvae of the Minnesota (MN) population had resistance ratios of 4.71 and >13.22 for Cry34/35Ab1 and Cry3Bb1 proteins, respectively, compared with the control colonies. In all on‐plant assays, the relative survival of the MN population on the DAS‐59122‐7 and MON88017 hybrids was significantly greater than the control colonies. Larvae of the MN population had inhibited development when reared on DAS‐59122‐7 compared with larvae reared on the non‐Bt hybrid, indicating resistance was incomplete. Overall, these results document resistance to Cry3Bb1 and an incomplete resistance to Cry34/35Ab1 in a population of WCR from a SmartStax ® performance problem field.